Combining Ability Analysis of Yield and Related Characters in Single Cross Hybrids of Tropical Maize (Zea Mays L.) - Sujiprihati, Sriani; Saleh, Ghizan; Ali, Eltahir Siddig (2001)
Twele mays (Zea mays L.) inbred parents previously selected for their performance were crossed in a diallel scheme. This were evaluated for general combining ability (GCA) and specific combining ability (SCA), at two locations in the University Putra Malaysia. The significant GCA and SCA effects observed reflected the importance of both additive and non-additive gene actions for yield and related characters in the hybrids. However, the SCA variances for all the characters studied were much higher than their respective GCA variances. Result of GCA variances showed that UPM-SM7-6, UPM-SW-9, and UPM-MT-13 were the best general combiners ( giving high positive effects) for grain yield and ear weight at both location. For days to teaseling, UPM-TW-5 and UPM-TW-12 were the best combiners for earliness (giving high negative GCA effects), at Field 2 and Share Farm respectively. For SCA effects, at Field 2, the highest significant positive effect for grain yield was shown by the cross UPM-SW-9 X UPM-SM5-5 which also gave the highest yield (4763 kg/ha). The highest SCA effect for ear weight were given by the cross UPM-SW-9 X UPM-SM5-9, while for plant height by the cross UPM-MT-13 X SM5-9. At Share Farm, the crossUPM-MT-5 X UPM-SM5-4 showed the best performance for grain yield (5948 kg/ha). This cross also gave the highest significant positive SCA effect for grain yield and ear weight. For plant height, the cross UPM-MT-5 X UPM- SM5-5 gave the highest SCA effect. The crosses UPM-MT-5 X UPM-SM5-5 and UPM-SW-9 X UPM-SM5-4 gave the highest negative SCA effects for days to maturity, at Field 2 and Share Farm, respectively, indicating their expression of genes for earliness in maturity. The hybrids showed a high range of performance for all characters investigated, and could be further exploited for their heterotic capacities.